The ballad of Lefty Brown [videorecording (DVD)] - Moshé, Jared; Pullman, Bill; Fonda, Peter, 1940-2019-; Caviezel, Jim, 1968-; Baker, Kathy, 1950- (Lions Gate Entertainment, 2018)
Set in the vast, desolate plains of Montana, it is an ode to the traditional revenge western. When famed frontier lawman and Montana's first elected senator Eddie Johnson is brutally murdered, his longtime sidekick and friend, Lefty Brown, will stop at nothing to avenge his death.